Impediment to Knowledge and Imagination in Ray Bradbury’s Dystopian Novel, Fahrenheit 451 - Emrah ATASOY (Ankara Üniversitesi Dil ve Tarih-Coğrafya Fakültesi Dergisi, 2017)
This article touches upon the critical, contextual and thematic analysis of Ray Bradbury’s dystopian novel, Fahrenheit 451(1953) to demonstrate how the totalitarian state envisioned in the book impedes imagination and knowledge. The protagonist, Guy Montag plays a pivotal role in reflecting the oppressive structure of the system and the possible consequences of defiance. The misuse of technology and banning of books shape monotype individuals thereby quite relevant to the discussion of the article. Thorough manipulation and control become instrumental in hampering knowledge and imagination. However, ultimately, such a repressive state does not wholly become successful in manipulating all citizens. The divergent individual whose awareness is aroused is turned into an isolated outcast by the system in this dystopian world. Although certain divergent characters cannot succeed in overcoming the system, they are functional in reflecting the failure of the system.